2017
DOI: 10.1136/bmj.j4849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weight loss interventions for adults who are obese on mortality, cardiovascular disease, and cancer: systematic review and meta-analysis

Abstract: Objective To assess whether weight loss interventions for adults with obesity affect all cause, cardiovascular, and cancer mortality, cardiovascular disease, cancer, and body weight. Design Systematic review and meta-analysis of randomised controlled trials (RCTs) using random effects, estimating risk ratios, and mean differences. Heterogeneity investigated using Cochran’s Q and I2 statistics. Quality of evidence assessed by GRADE criteria. Data sources Medline, Embase, the Cochrane Central Register of Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
257
2
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(294 citation statements)
references
References 94 publications
15
257
2
20
Order By: Relevance
“…From this analysis, it is not clear what factors would be responsible for driving greater weight loss in older patients. Notably, overall discontinuation results appeared to be lower for older patients in this analysis and therefore one could speculate that improved adherence could lead to improved weight loss outcomes . Improved weight loss outcomes for older patients has been noted previously in the literature .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…From this analysis, it is not clear what factors would be responsible for driving greater weight loss in older patients. Notably, overall discontinuation results appeared to be lower for older patients in this analysis and therefore one could speculate that improved adherence could lead to improved weight loss outcomes . Improved weight loss outcomes for older patients has been noted previously in the literature .…”
Section: Discussionsupporting
confidence: 64%
“…Notably, overall discontinuation results appeared to be lower for older patients in this analysis and therefore one could speculate that improved adherence could lead to improved weight loss outcomes . Improved weight loss outcomes for older patients has been noted previously in the literature . For example, a systematic meta‐analysis of randomized controlled trials evaluating weight loss interventions found some evidence that participants aged 60 or over lost more weight than younger participants .…”
Section: Discussionsupporting
confidence: 59%
“…In line with this hypothesis, the relationship between body mass index (which is a good epidemiological surrogate of insulin resistance) and risk of CVD death is non‐linear, both in subjects with and without T2DM . Moreover, dietary interventions aiming at reducing body weight have been recently shown to induce remission of T2DM while so far there is no clear experimental evidence of a reduced risk of CVD following weight loss interventions …”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the overall weight reduction of 1.2 kg in obese patients with OSA in the current study is of clinical relevance. According to a recent meta‐analysis of 34 randomized weight loss intervention trials, weight reduction of approximately 3.4 kg was associated with an 18% risk reduction of all‐cause mortality (Ma et al., ). This number corresponded to six deaths fewer per 1,000 participants.…”
Section: Discussionmentioning
confidence: 99%